Ownership structure as a corporate governance mechanism in Slovenian hotels - Knežević Cvelbar, Ljubica (Array, 2008)
Abstract: This paper analyses ownership structure and company performance in the light of corporate governance theory and the actual privatisation process. Previous research has proven that the Slovenian state is a poor and passive owner, whereas private owners and employees are more active and more interested in their company's economic performance. This paper shows that the transition to private ownership in the Slovenian hotel sector has not been finished. Consequently,state-owned and investment funds remain important owners of Slovenian hotels.The financial performance of hotel companies is below average in the economy and can be correlated with the current ownership structure. Since the current ownership structure has a negative impact on the hotel sector competitiveness,an ownership change is needed to boost the sector's competitiveness and the competitiveness of Slovenia as a tourist destination